18F FDG PET/MRI with hepatocyte-specific contrast agent for M staging of rectal cancer: a primary economic evaluation - Gassert, Felix; Rübenthaler, Johannes; Cyran, Clemens C.; Rink, Johann; Schwarze, Vincent; Luitjens, Johanna; Gassert, Florian T.; Makowski, Marcus R.; Schönberg, Stefan; Mayerhoefer, Marius E.; Tamandl, Dietmar; Froelich, Matthias F. (European journal of nuclear medicine and molecular imaging, 2021)
Rectal cancer is one of the most frequent causes of cancer-related morbidity and mortality in the world. Correct identification of the TNM state in primary staging of rectal cancer has critical implications on patient management. Initial evaluations revealed a high sensitivity and specificity for whole-body PET/MRI in the detection of metastases allowing for metastasis-directed therapy regimens. Nevertheless, its cost-effectiveness compared with that of standard-of-care imaging (SCI) using pelvic MRI + chest and abdominopelvic CT is yet to be investigated. Therefore, the aim of this study was to analyze the cost-effectiveness of whole-body 18F FDG PET/MRI as an alternative imaging method to standard diagnostic workup for initial staging of rectal cancer.